Identity Politics in Electoral Politics - Ahmad Zaini; Iin Ratna Sumirat; Moh. Zainor Ridho (UIN Sunan Gunung Djati, 2023)
Identity politics is interpreted as people's subconscious formation systems due to myriad social problems and dissatisfaction. Religion's politicization as a form of identity politics impacts the sustainability of democracy in Indonesia. This study uses a hybrid of primary and secondary data collection techniques. The primary data encompasses information from the executive, legislative, and judicial branches, intellectuals, scholars, academicians, mass organizations and NGO leaders, competent people in political corruption and elections, and researchers through direct, in-depth, and intensive interviews and testimonies. At least two important things are increasingly sticking out in the view above (populism and identity politics), which are intertwined to create actual political dynamics in the mayoral election in Serang City. In the political arena, populism is characterized by efforts to place the public as the mainstream and focal point. The problem is that populism is often held hostage as a means of reaching the center of power. Public participation in the discussion of public interest only appears in the short period leading up to the political competition. The victory can be seen among the candidates for mayor of Serang; there seems to be no significant difference between them because no ethnicity or race holds privilege. The dominant religion in this identity politics is the Muslim community, which the candidates are targeting because the people of Serang City are predominantly Muslim. Most of the elected mayor's votes prove that he has more value than other candidates. The relationship between religion and politics becomes problematic when it comes to the particularities of local politics, for example, the emergence of identity issues such as religious sentiment, ethnicity, son of the region, and majority. -minority. The issues of religion and ethnicity are considered applicable in regional head elections (Pilkada). The issue of religion and ethnicity (SARA) is considered the cheapest issue in the election context, manipulating the public's low education level.